Analytical performance test of silver nanoparticles citrate ( AgNPs-Cit ) ionic for chromium ( III ) ions determination - Syafriyanti Annur (Fak. Sains dan Teknologi UIN Sunan Kalijaga, 2019)
wt,1/irh,c.1